Biological nitrogen fixation by soybean (Glycine max [L.] Merr.), a novel, high protein crop in Scotland, requires inoculation with non-native bradyrhizobia - Maluk, Marta; Giles, Madeline; Wardell, Grace E.; Akramin, Aminin Taqrir; Ferrando-Molina, Francesc; Murdoch, Ashley; Barros, Marta; Beukes, Chrizelle; Vasconçelos, Marta; Harrison, Ellie; Daniell, Tim J.; Quilliam, Richard S.; et al. (Frontiers in Agronomy, 2023)
It is currently not recommended to grow soybean (Glycine max [L.] Merr.) further than 54° North, but climate change and the development of new high latitude-adapted varieties raises the possibility that it could be introduced into Scotland as a novel high protein crop deriving most of its nitrogen (N) requirements through biological N fixation (BNF). This was evaluated via field trials in 2017 and 2018 near Dundee (56.48°N). As there are no native soybean-nodulating bacteria (SNB) in UK soils, soybean requires inoculation to exploit its BNF potential. In 2017, three commercial inoculants containing elite Bradyrhizobium strains significantly increased plant biomass in plot trials with a soybean 000 maturity group variety (ES Comandor). Rhizobia were isolated from the nodules and identified as the original inoculant species, B. diazoefficiens and B. japonicum. One inoculant (Rizoliq Top) was used for larger-scale trials in 2018 with two varieties (ES Comandor, ES Navigator); inoculation doubled the grain yield to 1 t ha-1 compared to the uninoculated crop. The inoculated soybean obtained most of its N through BNF in both years regardless of plant genotype i.e. >73%Ndfa, with BNF contributions to aerial biomass exceeding 250 kg N ha-1 yr-1 in 2017 and that to grain 50 kg N ha-1 yr-1 in 2018. These data suggest that N-fixing soybean could be grown in Scotland without mineral N-fertiliser, either for forage as animal feed, or as green pods for human consumption (“edamame”), and potentially, even as dry grain. The potential for survival of the Bradyrhizobium inoculant strains in soils was also demonstrated through the detection of the inoculant strain B. diazoefficiens SEMIA 5080 at relatively high populations (104 g-1 dry soil) using a qRT-PCR method with SNB-specific nodZ primers. Microbiome data obtained from soil using 16S rRNA primers demonstrated that the diversity of bacteria belonging to the genus Bradyrhizobium increased in soybean-cropped soils compared to bulk soil regardless of inoculation status. The economic and practical implications of residual inoculum, as well as those arising from introducing a non-native plant and alien bacteria into Scottish soils in terms of their impact on the native soil microbiota are discussed.